The Effectiveness of Instagram Account @Bima.Kemdikbudristek as a Medium for Disseminating Information for Lecturers of Academic Education Colleges - Fuja Wahyudi; Ika Sartika (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
The Directorate of Research, Technology, and Community Service (DRTPM) disseminates research and community service information to lecturers of academic education colleges through social media @Bima.Kemdikbudristek. This study aims to analyze the effectiveness of the Instagram account @Bima.Kemdikbudristek as a medium for disseminating information to lecturers of academic education colleges using the AISAS method (Attention, Interest, Search, Action, and Share) as well as factors related to the effectiveness of Instagram. The research method used in this research is a quantitative method with a survey method. Respondents in this study were 101 academic education college lecturers who were obtained using quota sampling techniques. The results of this study indicate that the dissemination of information carried out by the @Bima.Kemdikbudristek Instagram account is effective for disseminating information to lecturers of academic education colleges, and there are factors related to the effectiveness of Instagram as a medium for disseminating research and community service information, namely information quality (completeness, relevance, accuracy, timeliness, and presentation of information). The results show that information quality has a very real relationship with the effectiveness of the Instagram account @Bima.Kemdikbudristek.